The recombination landscape of diploid wheat from a high-density genetic map of Triticum monococcum subsp. monococcum x Triticum monococcum subsp. aegilopoides - Amos, Cameron Henning (Kansas State University, 2022)
Einkorn wheat (Triticum monococcum), one of the oldest cultivated grains in the world, was domesticated during the early Neolithic period in South-Eastern Turkey. Einkorn played a critical role in supporting the unrivaled societal and population growth in and around the ‘Cradle of Civilization’. Einkorn wheat includes both wild einkorn (Triticum monococcum subsp. aegilopoides) and its domesticated form (Triticum monococcum subsp. monococcum), which is the only domesticated diploid wheat species. Another diploid A genome species morphologically similar to Triticum monococcum is Triticum urartu, being the direct source of the A-genome in tetraploid and hexaploid wheat. Triticum monococcum was cultivated for several centuries before free-threshing durum wheat (Triticum durum) and hexaploid bread wheat (Triticum aestivum) emerged from later hybridization events. The A-genome holds impressive nutritional content and high genetic polymorphism, and its genetic potential for wheat improvement has sparked renewed interest for this ancient crop. Here we investigate a mapping population of a cross between domesticated (Triticum monococcum subsp. monococcum) and wild einkorn (Triticum monococcum subsp. aegilopoides) to understand the structure, function, and evolution of the A genome. Two parents of a recombinant inbred line (RIL) population were sequenced to ~5x coverage to discover variants between the domesticated einkorn parent and the wild ancient progenitor parent. Two sets of derived RILs from these parents were skim-sequenced, including 93 RILs at 0.2x coverage and 786 RILs at 0.028x coverage. These populations were aligned to a newly developed reference for T. monococcum to identify recombination breakpoints in the RILs and evaluate the genome-wide recombination landscape in einkorn. We identified recombination hotspots and investigated the positional trends and associations within each chromosome between crossovers, genes, and variant SNPS. We observed a clear and strong positive correlation between the recombination density, gene density and distance from the centromere. There was a more drastic increase for both crossover and gene density with distance from the centromere observed than previously described in hexaploid wheat, rice, and maize. Regions with high crossover frequency reached ~3 cM/Mb in the short arms and ~1.5 cM/Mb in the long arms near the telomeres. Likewise, gene-rich regions were ~3x as gene-dense compared to proximal region of the same chromosome arm. Spikes in crossover frequency and gene density were also positionally correlated, especially within the distal halves of the arms. In this study we have demonstrated the utility of using very low coverage ‘skim-sequencing’ for accurate genotyping of genetic populations while revealing and comprehensive picture for the recombination and gene landscape of einkorn.
Keywords: Einkorn; Recombination; Bioinformatics; Genetics